BRAND AND PACKAGING DESIGN FOR VALUE-ADDED RICE PRODUCTS: A CASE STUDY OF PHO KLANG GERMINATED RICE COMMUNITY ENTERPRISES, NAKHON RATCHASIMA PROVINCE - Inthasang, Chatchai; Thongchai , Janpen; Nunnad, Purim; Kwamman, Yaowapa (Journal of Liberal Arts and Management Science Kasetsart University, 2021)
The objectives of this research were to design the brand and package of rice products and to study the satisfaction towards brand and packaging: a case study of Pho Klang Germinated Rice community enterprises in Nakhon Ratchasima. This research was a mixed method. The first phase was qualitative research by using semi-structured in-depth interviews. Collected data from 8 community enterprise leaders to obtain guidelines for brand and packaging development. The second phase was quantitative research. A questionnaire was used for data collection. This study comprised of a sample population of 400 customers in Nakhon Ratchasima municipality, using a purposive sampling method. Statistics using in analyzing the data were percentage, mean, standard deviation, and multiple regression analysis. The qualitative research results illustrate that adding value by branding and packaging design make rice products outstanding, identify of the community through the brand and, add value of the product. While, the quantitative research results of hypothesis testing found that brand and packaging play a significant and positive effect on customer satisfaction. The results can be applied by other community entrepreneurs to satisfy genuine needs of consumers.